Scoringowa metoda pomiaru lojalności klientów zakładów ubezpieczeń działu II - Rodzinka, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper aim is to choose method of measuring loyalty of customers of nonlife insurance companies. The author uses results of research conducted in period March-April 2003 on 772 households and 739 companies from podkarpackie voivodeship. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 339-353